2002
DOI: 10.1159/000065275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intrauterine Growth Retardation on the Progression of Nephrotic Syndrome

Abstract: Background/Aim: Neonates with intrauterine growth retardation (IUGR) experience higher morbidity and mortality rates than appropriate-for-gestational-age (AGA) neonates. The purpose of our study was to clarify whether IUGR has any influences on the progression of nephrotic syndrome in children. Methods: We performed a retrospective review of 56 children with nephrotic syndrome. IUGR was defined as a birth weight less than the tenth percentile for gestational age. Among 56 patients having nephrotic syndrome, 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 20 publications
1
26
0
2
Order By: Relevance
“…This could explain associations of low BW with such clinical outcomes as albuminuria, low-normal kidney function, and ESRD. [6][7][8][9][10][11][12][13][14][15][16][17]37 However, these are only a few studies, sometimes with a weak design, and the effects found were not strong. Case-control studies showed an OR of 1.5 for ESRD in subjects with BWs less than 2,500 g, but data for BW were missing in half the cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could explain associations of low BW with such clinical outcomes as albuminuria, low-normal kidney function, and ESRD. [6][7][8][9][10][11][12][13][14][15][16][17]37 However, these are only a few studies, sometimes with a weak design, and the effects found were not strong. Case-control studies showed an OR of 1.5 for ESRD in subjects with BWs less than 2,500 g, but data for BW were missing in half the cases.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] The clinical consequences of these alterations were investigated at different levels, and associations were found of IUGR with microalbuminuria, 11,12 faster progression of renal dysfunction in patients with specific kidney diseases, 13,14 and end-stage renal disease (ESRD). 15,16 Because IUGR also was associated with other diseases, such as type 2 diabetes mellitus, it is difficult to disentangle direct from indirect effects of IUGR on advanced renal failure.…”
Section: Introductionmentioning
confidence: 99%
“…67,115,132 More rapid progression or relative resistance to therapy was also observed in LBW individuals with IgA nephropathy, membranous nephropathy, minimalchange disease, nephrotic syndrome, and chronic pyelonephritis. [132][133][134][135][136][137][138] Among a predominantly black dialysis population, the odds ratio for ESRD was 1.4 (95% confidence interval 1.1 to 1.8) among those with LBW compared with those with NBW. 16 This relationship persisted for all causes of ESRD and was not affected by family history of ESRD.…”
Section: Measures Of Renal Functionmentioning
confidence: 99%
“…Furthermore, adults with the lowest kidney volumes, examined in the context of current weight, had the highest rates of albuminuria and highest BP (23), tending to support a role of nephron underdosing in these pathologies. Lower birth weights have been associated with higher relapse rates in children with the nephrotic syndrome (86,87) and with progression in children with IgA nephropathy (88). Associations of birth weight with renal deaths are obscured by the competing effects of the higher numbers of cardiovascular and other nonrenal natural deaths that are predicted by renal markers (75)(76)(77)89) and by deficient documentation of the contribution of renal disease to natural deaths (90).…”
Section: Low Nephron Number Renal Disease and Renal Failurementioning
confidence: 99%